A study of di(amino)stibines with terminal Sb(iii) hydrogen-ligands by X-ray- and neutron-diffraction12. Issue 9 (11th February 2019) - Schwamm, Ryan J.; Edwards, Alison J.; Fitchett, Christopher M.; Coles, Martyn P.
Abstract : The structure of a di(amino)stibine has been determined by neutron diffraction giving the first accurate parameters for the Sb III –H bond. Abstract : The bis(amidodimethyl)disiloxane ligands [OSiMe2 NR2 ] 2− (R = 2, 6-Me2 C6 H3 (Ar′) and 2, 6-iPr2 C6 H3 (Ar), abbreviated [NON R ] 2−, are a stable support for Sb(iii ) complexes of general formula Sb(NON R )X (X = Cl, H). The compounds are monomeric in the solid-state, with bidentate N, N ′-coordination of the [NON R ] 2− and terminal chloride/hydrogen-ligands. Sb(NON Ar′ )H was analyzed by single-crystal neutron diffraction, giving the first accurate parameters for the Sb–H bond to an antimony(iii ) centre.